Soil microbial populations in Felda oil palm plantation in Jengka 24, Malaysia - Low, Ying Chiang (2015)
The main objective for this research was to analyse soil microbial diversity in the oil palm plantation in order to understand the soil microbial community which could help to formulate new and innovative management of the basal stem rot (BSR) disease. Soil sampling was conducted at FELDA Jengka 24. Sampling areas include sites with empty fruit bunches (EFB) application, high BSR incidence and no BSR incidence. For comparisons, soils from the adjacent forest were sampled. Plate count technique was adopted for evaluation of overall soil microbial populations. Functional microbes were evaluated using specific media. Identification and characterisation of functional microbes were carried out by molecular means. BIOLOG EcoPlate was used to analyse microbial community. Plate count data (Colony forming unit = CFU) were subjected to Student’s t-Test for significance test. Optical density (OD) values from the BIOLOG EcoPlate were subjected to Principal Component Analysis (PCA). Results showed that significant difference was not detected for fungal populations in EFB applied versus non-EFB applied sites. Similar observations were recorded for bacterial and actinomycetes. This has indicated that EFB application didn’t seem to affect fungal, bacterial and actinomycetes populations. Although non-significant differences were reported for fungal, bacterial and actinomycetes in high BSR versus BSR-free sites, observations that prompt further investigations were discovered. Fungal population in high BSR sites fluctuates, ranging between 3.2x102 to 2.3x105 CFU/gram, as opposed to stable bacterial and actinomycetes populations. Sites with low fungal but high bacterial count could be potential indicator for BSR infestation. Phosphates solubilisers assessments revealed that they were not influenced by BSR incidence, supported by non-significant difference with average population of 1x105 CFU/gram. Similar observations were recorded for nitrogen fixers. Although not significantly different, lignin degraders in BSRfree sites (average 1.3x103 CFU/gram) were higher than BSR infested sites (average 63 CFU/gram). This has suggested that soils with low lignin degraders are conducive for BSR. EFB applied sites recorded with significantly higher lignin degraders population, indicating EFB contributing to lignin degraders. Pseudomonas and Bacillus bacteria were not affected by BSR incidence indicated by significance test. EFB applications seemed to contribute to both with high and consistent population with average count of 2.13x106 CFU/gram and 1.2x104 CFU/gram for Pseudomonas and Bacillus respectively. Trichoderma sp. fungi with average 2.8x104 CFU/gram population was not affected by BSR incidence and EFB application. A total of 27 microbes from various functional groups were identified including bacteria (Burkholderia sp., Klebsiella sp., Bacillus sp., Chryseobacterium sp.,Streptomyces sp., Chromobacterium sp., Pseudomonas sp.) and fungi (mainly from orders Hypocreales and Eurotiales). PCA for microbial community assessment have revealed the closely related microbial communities in oil palm cultivated sites. In contrast, sparsely tabulated data points recorded for forests soils indicated low relative similarity of microbial communities. These results were further supported by analysis of carbon sources utilisation. The PCA analyses for EFB and non-EFB applied sites yielded non-distinct difference, indicating high relative similarity of microbial communities in both sites. It has also indicated that the application of EFB might not cause drastic changes to the soil microbial community. Similarly, PCA analyses for microbial communities in high BSR and BSR free sites yielded high relative similarity. The closely related microbial communities in BSR and BSR free sites also indicated that BSR disease infestation did not seem to affect soil microbial communities. Both comparisons above demonstrated presence of stable resilient microbial communities in oil palm soils. This research will provide valuable information on soil microbial community in oil palm soil and draw leads for future research.